The Advocacy of Disability Service Unit in the Education Sector in the City of Surabaya - Sugihermanto Sugihermanto; Atung Yunarto; Tutus Setiawan; Gunawan Tanuwidjaja; Saraswati Ayu Indhiraswari; Dian Wulandari (International Journal of Disabilities and Social Inclusion, 2021)
Republic of Indonesia’s Act No. 8 of 2016 recommends the guarantee for People with disabilities’ right to live, including education. It turns out that, on the other hand, most people with disabilities (pwds) in Indonesia live in vulnerable, underdeveloped, and poor conditions. Therefore, certain endeavours need to be done to realize the equal rights of pwds towards a prosperous, independent, and non-discriminatory life, through the establishment of a Disability Service Unit. Unit Layanan Disabilitas (abbreviated as ULD - Disability Service Unit) in the education sector is an important part of the Regional Government body (Provincial and Municipality) which functions as a provider of services and facilities for pwds. Hence, its presence is very important for the lives of pwds. Lembaga Pemberdayaan Tunanetra (LPT—Blind Empowerment Institute) is a non-governmental organization (NGO) that is engaged in advocacy, education, and research related to disability. LPT has drafted East Java’s Governor Regulation and Surabaya’s Mayor Regulation regarding the Implementation of Inclusive Education as legal protection. Regarding this Disability Service Unit (ULD), Petra Christian University (PCU) has formed Unit Layanan Disabilitas dan Pengguna Khusus (abbreviated as ULDPK - Disability and Special User Services Unit) since April 12, 2017 in the PCU Library. This Services Unit has facilitated several users with special needs to try to borrow books, accessing library services, and was assisted by librarians, lecturers, and eight students in 2017. This effort was redeveloped again in April and May 2018 to share the importance of the Educational ULD and PCU Library’s ULDPK to various Provincial Offices, Municipal Offices, Non-Governmental Organizations, Special Schools, and Inclusive Schools for two weeks. This activity was very impactful in strengthening the concept of inclusive development, especially on increasing the awareness of various parties about the importance of Educational ULD in the City of Surabaya.